BERBAGAI FAKTOR YANG MEMPENGARUHI KEBERHASILAN PEDAGANG SEKTOR INFORMAL DI KOTAMADYA SURAKARTA - TRIO HANDOKO (MANAJEMEN DAN KEUANGAN, 2011)
Research which title “Many factor which affected succesfully carry out on trader informal sector in Surakarta 5 distrik. That Research direction to acquire ilustrate how much absorbstion employee or prosect which to receive (cacth) in activity informal sector in the prior food-night trader, for knowing how internal and eksternal factor to affected succesfully his work, and for knowing what night trader have clown/ actor in happen City arsitecture which discipline and harmony. Teknique taking sample carry out with random sampling sample-consist 30% all total night trader from 5 district in Solo City. Method data analysis which employee is Validiti and realibility in corelation moment product and Kai Kuadrat Analyisis. From data analyis know that from data validity poin real valid and good. This poin seeing that re from moment product. And from reliabilitas poin data showed corelation : 0,834 that means stable enough, cause r (0,834) from r moment product (0,532).